Correction: An initiative to develop capability-adjusted life years in Sweden (CALY-SWE): Selecting capabilities with a Delphi panel and developing the questionnaire. - PLOS One Editors (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0263231.].